Leasing, the leasing process, leasing relations in the activities of small and medium-sized enterprises (Journal of Economic Research & Business Administration, 2017)
The article discusses the development of new types of lending, bothin cash and in the form of commodities, in particular the leasing activity,becoming an important lever for the activation of innovative activity in theenterprises and the expansion of business in the modern conditions. Theparticular importance of leasing was highlighted as investment tool, acquiringan significant role in the conditions of economy transformation andmodernization of material-technical base in the production. It is shown,that the use of leasing relations activates the investment of private capitalin the production sphere, improve the financial condition of the producersand increase the competitiveness of small and medium-sized businesses,whose work is an additional resource for the development of the complexin the country and its regions.